Digital silence and linguistic invisibility: muted participation in online learning - Bazlan, Anis Shahira; Amir Yazid, Amirah Athirah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
When universities across Malaysia shifted their classes online during the COVID-19 pandemic, educators and students faced a new reality, which is teaching and learning through screens. Through these events, something else quietly emerged in those virtual classrooms: silence. It was not just any occasional quietness but a persistent absence of voices. A few students engaged in class discussions, and none unmuted their microphones or turned off their cameras. At first glance, it may appear to be disengagement, but for many of us who teach, observe, and reflect, we have realised that this ‘digital silence’ is not just about laziness or distraction. It is far more layered. As educators, we might recall posing a straightforward question in our online language classes. “Can someone explain the meaning of this paragraph to me?” Silence. Then, a quiet “not sure, Miss” appeared in the chat box, followed by a smiley emoji, or there was generally no emoji given at all. No voices. We received no further responses. This repeated scenario led us to look deeper.